2019
DOI: 10.17532/jhsci.2019.818
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence to Type 2 Diabetic Patients Hospitalized at a Tertiary Care Hospital in Bangladesh

Abstract: Background: Diabetes Mellitus (DM) has been a global epidemic in the new millennium and the majority of all diabetic patients constitute Type 2 diabetes mellitus. Medication adherence to prescribed treatments is a key determinant to achieve therapeutic success reduces diabetic complications. Objectives: The aim of the study was to examine the level of medication adherence to Type 2 diabetic patients hospitalized at tertiary care hospital in Bangladesh. Methods: The study was descriptive cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
4
6
1
Order By: Relevance
“…A study implied that patients typically perceived to be healthy including those who were new to diabetes and on few other medications, may be at risk for non-adherence 12 . Although there were studies showing that patients with comorbidities may have worse medication compliance 12 , 17 , our subgroup analysis revealed those with high CIC or DCSI had better compliance. This might be due to the wide coverage and extremely low co-payment of our National Health Insurance policy.…”
Section: Discussioncontrasting
confidence: 55%
“…A study implied that patients typically perceived to be healthy including those who were new to diabetes and on few other medications, may be at risk for non-adherence 12 . Although there were studies showing that patients with comorbidities may have worse medication compliance 12 , 17 , our subgroup analysis revealed those with high CIC or DCSI had better compliance. This might be due to the wide coverage and extremely low co-payment of our National Health Insurance policy.…”
Section: Discussioncontrasting
confidence: 55%
“…al reported that 25.9% of diabetes patients in a tertiary hospital sometimes forgot to take their medications, while 1.8% often forgot. 29 Our findings of low medication adherence are in line with a previous report from India that found the prevalence of low medication adherence to be 51.7% using the MMAS tool. 34 However, the lack of standard measurements for medication adherence, the difference in the sample population, and the use of different definitions for glycemic control make comparisons between studies challenging.…”
Section: Discussionsupporting
confidence: 92%
“…38 Our study suggested that low medication adherence was significantly higher among younger people which is in line with a study by Rana et.al. 29 A similar study by Ahmad et al in patients with Type 2…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This finding could be because younger patients take better care of their health to ensure a long healthy life, and the elderly seem to fear complications and mortality. This reported adherence rate was consistent with the previous findings [25,26]. Moreover, older patients who suffer from comorbidities should have more medicines on their prescription, and polypharmacy is a potential factor for medication nonadherence [27].…”
Section: Discussionsupporting
confidence: 91%